Hydrological niche separation between two coexisting shrubs in an extremely arid region - Mingyan Fan; Hai Zhou; Lihui Tian; Heng Ren; Bing Liu; Xibin Ji; Xiangyan Feng; Qiyue Yang; Huli Gu (Journal of Hydrology: Regional Studies)
Study region: At the southern edge of Badain Jaran Desert, China. Study focus: The mixed shrubs of Calligonum mongolicum and Nitraria sphaerocarpa are the common species in extreme arid areas. There are few studies on the water use and coexistence mechanisms of the two species. So we examined the water use strategies of these two species based on hydrogen and oxygen stable isotope technology, and the coexistence mechanism of the two desert plants was explored from the perspective of hydrological niche separation (HNS). New hydrological insights for the region: The N. sphaerocarpa had more root biomass in shallow soil than C. mongolicum, whereas the opposite was true in deep soil, indicating a root niche separation. Additionally, the C. mongolicum exhibited a significant dependence on deep soil water (about 26 %) and groundwater (over 30 %); while N. sphaerocarpa has a significant response to precipitation, its proportion of shallow soil water is more than 40 % after heavy precipitation events, in seasons with less precipitation, it relied on groundwater for survival. Both species had a dynamic HNS, the hydrological niche overlap index exhibited a decreasing and then increasing trend; but HNS was low during the dry season, indicating that HNS was affected by precipitation. We conclude that the main reason why the two species can coexist in arid regions is their HNS, which avoid competition for limited water resources.